Civil Liability of E-Commerce Platform Operators in Korea (Focusing on the P2C Relations) - Seo, Heesok (Universitas Airlangga, 2025)
This paper introduces and analyzes Korean law regarding the civil liability of e-commerce platform operators or intermediaries. The E-Commerce Act in Korea outlines three basic liabilities and two enhanced liabilities for these intermediaries. The Act requires intermediaries to notify consumers that they are not parties to the sales contract and to provide the seller's identity information, clarifying the party responsible for the contract. It also mandates that intermediaries handle complaints and disputes arising from transactions, acting as moderators between sellers and consumers. The enhanced liabilities address intermediaries who are also sellers or those involved in transactions, aiming to protect consumers by recognizing the intermediary's liability as a seller or on behalf of a seller. Ongoing debates exist about the basis for attributing responsibility and the effectiveness of these two enhanced liabilities. The paper concludes that the three basic liabilities are more crucial than the two enhanced ones, with the duty to handle complaints and disputes being particularly important for consumer protection. Recent developments in self-regulation reflect a constructive market response, aligning with the characteristics of Korean law.